Work stress, age, and years of service with feeling of work fatigue among nurses at Grhasia hospital Yogyakarta - Angelina Candra Dewi; Agus Surono; Adi Heru Sutomo (Fakultas Kedokteran Universitas Gadjah Mada, 2016)
Work stress, age, and years of services with work fatigue among nurses at mental hospital of Grhasia YogyakartaPurposeThis research aimed to find associated factors of working stress, age, and working length with fatigue feelings among nurses at mental hospital of Grhasia Yogyakarta. MethodsA cross-sectional study was conducted using data sheets, job stress questionnaire, and KAUPK2 questionnaire given to 55 nurses. Research data were analyzed using Pearson product moment and multiple linear regression tests. ResultsWork stress correlated with work fatigue feelings with value r=0.454, p-value<0.05, age correlated with feelings of work fatigue with value r=0.334, p-value<0.05, and working relationship with feelings of work fatigue with value r=0.361, p-value<0.05. The results of multiple regression analysis indicated that job stress and work period have a significant relationship and are the factors that most play a role in determining feelings of work fatigue among nurses (R2=0.275, p=0.000).ConclusionThere was a correlation between work stress, age, and work period with feelings of work fatigue among nurses, and there were influences simultaneously between work stress and work period with feeling of work fatigue. It is recommended for hospitals to conduct recreational activities or rotate work for senior and less productive nurses with junior and productive nurses. This policy aims to eliminate boredom and work fatigue. In addition, nurses are expected to perform and improve healthy lifestyles, by performing routine medical check ups, eating food with a balanced diet and getting adequate rest.